Violent recidivism of mentally disordered offenders: the development of a statistical prediction instrument - Harris, Grant T. - (Criminal justice and behavior, 1993)
Multivariate techniques were used to derive and validate an actuarial instrument for the prediction of violent postrelease offenses by mentally disordered offenders. The 618 subjects were a heterogeneous group of men who had been charged with serious offenses. Approximately half had been treated in a maximum security psychiatric institution and the rest had been briefly assessed prior to imprisonment. The actuarial instrument consisted of 12 variables and significantly predicted violent outcome in each of five subgroups. The instrument's practical application and its use in clinical appraisals of dangerousness are discussed